AN ANALYSIS OF STUDENTSâ GRAMMATICAL ERRORS IN USING TENSES IN WRITING ANALYTICAL EXPOSITION TEXT: A Case Study at the Class IVD of English Department of STKIP-PGRI Bandar Lampung in 2012/2013 - Subari, Imam (Lentera: Jurnal Ilmiah Kependidikan, 2013)
As an international language, English is used by people all over the world. It becomes a tool to communicate and build relationship and cooperation in many sectors such as education, health, economy, science and technology. Realizing the importance of English, in Indonesia, English is taught as a compulsory subject from junior high school to university or college level. It is also taught in elementary school as local content. The problem that is stated in this research is that the students still often make grammatical errors in using tenses in writing analytical exposition text. Writing is difficult language skill to be mastered by the students. In writing, the students must master and know the knowledge of grammar so that the students do not make errors, especially in using tenses in their writing.The objectives of this research are to know and describe studentsâ tenses mastery, to know and describe studentsâ grammatical errors in writing analytical exposition text, and to know and describe the types of errors the students make in using tenses in writing analytical exposition text. The population of the research is the students of class IVD at English Department of STKIP PGRI Bandar Lampung. The total number are 40 students of this research. In collecting the data, the writer used writing test by asking students to make analytical exposition text in using tenses. To analyze the data and take the last conclusion, the writer used percentage formula.Based on the data analysis, the writer found 476 sentences; there were 95 incorrect sentences or 19.95 %. The incorrect sentences consist of omission error was 32 sentences or 6.72%, addition error was 25 sentences or 5.25%, misformation error was 32 sentences or 6.72% and misordering error was 6 sentences or 1.26%. It can be seen that the studentsâ ommision and misformation error were the highest error and the studentsâ misordering error was the lowest error.